FIVE BASIC TENSES - S.B PANGGABEAN (VISION, 2016)
Students have different opinion on the using of five basic tenses. Questions were asking to students about the tenses. To prove the statement is true or wrong , so we gave the question to PBI 5/4th semester about five basic tense evidently they can answered the question and just some of them who can’t answered. Only one student categorized as Excellent, only 18 students  categorized as Very Good, only  6 students categorized as Good and only one student categorized as Poor. But the problem of them is they not really know about the distinguish how to use Future tense and Past Perfect tense, Simple present tense and Present continuous tense and the last Present perfect tense and Present continuous tense.